The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.21470/1678-9741-2022-0378
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Calcium Level and C-Reactive Protein Albumin Ratio Affect Severe Bleeding After Coronary Artery Bypass Grafting

Serdar Badem,
Ahmet Yuksel,
Ali Onder Kilic
et al.

Abstract: Objective In this study, we aimed to determine whether plasma calcium level and C-reactive protein albumin ratio (CAR) as well as other demographic and hematological markers are related in predicting severe bleeding after coronary artery bypass grafting (CABG). Methods A total of 227 adult patients who underwent CABG at our hospital between December 2021 and June 2022 were prospectively studied. Total amount of chest tube drainage was evaluated within the first 24 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We have read the article by Badem et al [ 1 ] entitled “Plasma Calcium Level and C-Reactive Protein Albumin Ratio Affect Severe Bleeding After Coronary Artery Bypass Grafting” with great interest. First of all, we congratulate the authors for their valuable contribution to the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have read the article by Badem et al [ 1 ] entitled “Plasma Calcium Level and C-Reactive Protein Albumin Ratio Affect Severe Bleeding After Coronary Artery Bypass Grafting” with great interest. First of all, we congratulate the authors for their valuable contribution to the literature.…”
mentioning
confidence: 99%
“…In that current study, the authors concluded that parameters such as albumin, calcium, and C-reactive protein from preoperative blood values may have an effect on postoperative bleeding [ 1 ] . All patients underwent coronary artery bypass grafting (CABG) operation accompanied by cardiopulmonary bypass (CPB).…”
mentioning
confidence: 99%